2019
DOI: 10.1029/2018rs006636
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Parameters of Frequency Dispersion for Radio Links of Different Length Using Software‐Defined Radio Based Sounding System

Abstract: Methods and relevant software were developed to study frequency dispersion parameters of wideband high‐frequency (HF) radio channels over propagation paths of different lengths: near vertical incidence skywave paths (up to 500 km) and long‐distance radio paths (from 1,000 up to 3,500 km). We developed a universal ionosonde (in terms of methods and signals) to do experimental research into HF radio wave propagation and dispersion using software‐defined radio technology and platform Universal Software Radio Peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…FR is measured through the channel testing by a spread spectrum signal that allows its compression in the receiver. Previous studies [4] showed that a compressed signal is related to a channel IR. Procedure involves testing of a frequency-ordered set of adjoint narrowband ch  channels that constitute a wideband one.…”
Section: Methods Of Measuring Wideband Radio Channel Frmentioning
confidence: 98%
See 3 more Smart Citations
“…FR is measured through the channel testing by a spread spectrum signal that allows its compression in the receiver. Previous studies [4] showed that a compressed signal is related to a channel IR. Procedure involves testing of a frequency-ordered set of adjoint narrowband ch  channels that constitute a wideband one.…”
Section: Methods Of Measuring Wideband Radio Channel Frmentioning
confidence: 98%
“…Currently, the main approach to solving the problems of radio wave propagation is an equivalence principle. According to that principle radio channel can be modeled by an equivalent linear system [4][5][6][7]…”
Section: Theoretical Fundamentals Of Channel Adaptive Equalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The variability of the propagation medium requires the development and study of the corrector training mode by means of data on sounding throughout the transionospheric radio channel. Previous research [2][3][4] showed that the frequency dispersion parameters, and, consequently, the transionospheric radio channel characteristics, depend on the total electron content (TEC) of the ionosphere. Since experimental estimates contain stochastic errors, it is crucial to perform an analysis of the influence of this factor on the correction performance.…”
Section: Introductionmentioning
confidence: 99%